Heterosis and inbreeding depression in relation to heterotic parameters in bread wheat (Triticum aestivum L.) under late sown condition - Kumar, JayDev; Kumar, Arun; Kumar, Mukul; Singh, Sanjay Kumar; Singh, Lokendra; Singh, Gyanendra Pratap (Journal of Cereal Research, 2017)
The present investigation on heterosis and inbreeding depression was conducted on genetically diverse 10 parent diallel crosses of bread wheat. The experimental materials comprised 100 genotypes including 10 parents and their F1s and F2s progenies and trial was conducted in randomized complete block deign with three replication at Economic Botanical Research Farm, Nawabganj of C.S. Azad University of Agriculture and Technology, Kanpur, Uttar Pradesh, India, during 2013-14 and 2014-15. The analysis of variance revealed that the all components of variances showed significant differences for almost the traits under studied over both generations. The result of economic heterosis revealed that the cross combinations, DBW 14/K 0424, K 9162/K 9423, K 9533/K 0307, K 1114/K 0424 and K 1114/NW 2036 were good for grain yield per plant along with range of -88.54 (K 0424/K 0911) to 28.52 per cent (DBW 14/K 0424) and other traits compared to 45 F1s whereas, all these cross combinations also had significant grain yield demission in F2s results of increase of homozygosity among the crosses in succeeding generations. The range of inbreeding depression varied from- -50.36 (K 1114/K 9423) to 49.12 percent (K 0911/K 0307) in F2s. Accordingly, these cross combinations may be utilized for improving grain yield as well as production of better transgressive segregants in advance generations for maintaining of specific gene pool of bread wheat through breeding program in future. DOI:10.25174/2249-4065/2017/67482